PARENTS ANXIETIES IN CARING FOR CHILDREN WITH HIV / AIDS - Ellya Susilowati; Juariah Marwah Dikiyah (Indonesian Journal of Social Work, 2019)
This study examines the parents’ anxiety in parenting children with HIV/AIDS at Yayasan Pelita Ilmu Jakarta. The purpose of this study to obtain an empirical description of the characteristics of respondents and the physical condition related anxiety. The method used in this research is quantitative approach. The sample size of this research is 30 people taken by cluster sampling technique. Data collection techniques used were questionnaires and documentation studies. The results show that parents who have children with HIV/AIDS experience anxiety in parenting. Respondents have severe anxiety on physical aspect equal to 53,33%, This anxiety is most dominantly triggered by fears of stigma and discrimination, as well as the health conditions of children with HIV / AIDS which are vulnerable. The results of the research problem analysis require problem-solving efforts so that researchers propose an anxiety program reduction for parents of children with HIV/AIDS. This program aims to improve the parents’ skills in dealing with situations that could be trigger their anxiety.